Dampak Penerapan Pembelajaran Berdiferensiasi pada Keterlibatan Siswa di Kelas Multikultural di SMA Kota Makassar - Sadriani, Andi; GH2, Muliana (Peneliti.net, 2024)
This study aims to determine the impact of the implementation of differentiated learning on student engagement in multicultural classes in high schools in Makassar City. The method used in this study is descriptive qualitative research with 10 informants of high school teachers who have implemented differentiated learning strategies. Data collection was carried out through in-depth interviews and participant observation. Data analysis was carried out using thematic analysis, namely by transcribing interviews and observation notes, then coding to identify the main themes. The results of the study showed that the implementation of differentiated learning had a positive impact on student engagement in multicultural classes. First, there was an increase in students' cognitive engagement, where students became more active in asking questions, engaging in group discussions, and feeling more confident when assignments were tailored to their interests and abilities. Second, students' emotional engagement also increased, especially because students felt valued and supported by teachers who paid attention to their individual needs and cultural backgrounds. Third, students' behavioral engagement became more active and dynamic, with increased participation in collaborative activities such as group projects and presentations. Overall, integrated learning in multicultural classes was able to significantly increase students' cognitive, emotional, and behavioral engagement.